Influence of type and amount of straw cover on weed emergence - Correia, N. M.; Durigan, Julio Cezar [UNESP]; Klink, U. P. (Marcel Dekker Inc, 2005)
This research was undertaken during 2003-2004 growing season to evaluate the effects of type [forage sorghum hybrid Cober Exp (Sorghum bicolor x Sorghum sudanense), forage millet (Pennisetum americanum var. BN2), finger millet (Eleusine coracana), and St Lucia grass (Brachiaria brizantha)] and amount of straw cover (5.5 and 3.0 t ha(-1)) upon the emergence of Bidens pilosa, Chamaesyce spp., Amaranthus spp., and Commelina benghalensis, under field conditions of the Brazilian Cerrado, in the region of Uberlandia-MG. The control consisted additional treatment lacking the straw cover. Emergence of weed depended on the type and amount of straw cover, as well as the weed species. The lowest number of B. pilosa seedlings was found in the presence of forage sorghum straw; Chamaesyce spp. in the lack of straw; Amaranthus spp. in the presence of higher amount of forage sorghum and forage millet, and lower amounts of forage millet and Finger Millet. All the types and amounts of straw reduced the emergency of C. benghalensis, except at the lowest level of St Lucia grass and the lack of straw.
Keywords: Sorghum bicolor x Sorghum sudanense; Pennisetum americanum; Brachiaria brizantha; Eleusine coracana